PENGARUH DISIPLIN KERJA, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI ( Studi Pada Balai Besar Wilayah Sungai Pemali Juana ) - Khasifah, Fikratunil; Nugraheni, Rini (Diponegoro Journal of Management, 2016)
This research is motivated by the phenomenon of employee performance declined at the Great Hall of the Basin Pemali Juana. The reduced performance is due to the employee for breach of discipline, uneven workload and work environment that is less comfortable. The purpose of this study was to analyze the influence of labor discipline, workload and work environment to employee performance Great Hall of the Basin Pemali Juana.Analysis of the data used in this study is descriptive and quantitative. The sampling in research using techniques Proportionate Stratified Random Sampling. The data was collected using a questionnaire distributed to 69 employee ofÂ  Great Hall of the Basin Pemali Juana. Based on theÂ  multiple linear regression test, the results show that the work discipline have a positive relationship and a significant influence on the employee performance. Work environment has a positive and significant impact on the employee performance. While the workload has a positive relationship, but no significant effect on the employee performance.